Bleomycin inhibits adipogenesis and accelerates fibrosis in the subcutaneous adipose layer through TGF‐β1. Issue 11 (29th October 2013) - Ohgo, Shiro; Hasegawa, Seiji; Hasebe, Yuichi; Mizutani, Hiroshi; Nakata, Satoru; Akamatsu, Hirohiko
Abstract: Systemic sclerosis [scleroderma (SSc)]‐associated skin fibrosis is characterized by increased fibrosis in the dermis and a reduction in the thickness of the subcutaneous adipose tissue layer. Although many studies have examined fibrosis in SSc, only a few studies have focused on the associated reduction in the thickness of the subcutaneous adipose tissue layer. In this study, we investigated the effects of SSc‐induced fibrosis on adipose tissue. We found that bleomycin suppresses adipogenesis in adipose‐derived stem cells (ASCs) and stimulates ASCs to express transforming growth factor β1 ( TGF‐β1 ), which suppresses adipogenesis and promotes fibrosis. Furthermore, we found that adipocyte‐conditioned medium suppressed collagen synthesis by fibroblasts in fibrosis‐like conditions. We concluded that in the skin affected by bleomycin‐induced fibrosis, increased TGF‐β1 expression suppresses adipogenesis and promotes adipocyte fibrosis. It was also suggested that adipocytes have an inhibitory effect on the progression of fibrosis.